Analisa Kinerja Keuangan pada Koperasi Uber Kepanjen melalui Rasio Likuiditas, Solvabilitas dan Profitabilitas - Angguliyah Rizqi Amaliyah; Muhamad Mahrus Alie (INVENTORY: JURNAL AKUNTANSI, 2020)
An assessment of the performance of a financial institution can be done by analyzing its financial statements. With the aim to find out how much the financial performance of the Kepberen Uber Cooperative is in a healthy condition. This financial performance is reviewed through an analysis of its financial ratios. In this study, researchers used a descriptive analysis with a quantitative approach. Taking the research subject at the Kepanjen Uber Cooperative. While the object of research taken was the annual report of the Kepberen Uber Cooperative starting the period 2016 - 2018. Research conducted shows that the Liquidity Ratio with the type of Current Ratio gives fairly healthy results for its financial performance, and gives an unhealthy financial performance results on its Cash Ratio type. Solvency ratios measured by the type of Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR) that provide financial performance results in a healthy condition. Profitability ratios measured by the type of Return on Equity (ROE) provide financial performance results in an unhealthy condition, in the type of Return on Assets (ROA) provide financial performance results in a fairly healthy condition, and Net Profit Margin (NPM) which provides performance results financial condition is very healthy. Thus the results of the analysis of financial performance in the financial statements of the Cooperative Uber Kepanjen through financial ratio analysis has been classified as good even though the performance of the cooperative has decreased each year and fluctuations.Keywords: Financial performance, Liquidity Ratios, Solvency Ratios, Profitability Ratios